Dynamic mechanical stimulation of alveolar epithelial-fibroblast models using the Flexcell tension system to study of lung disease mechanisms - Safiya Al Yazeedi; Tony Ju Feng Guo; Tony Ju Feng Guo; Joban Sohd; Filsan Ahmed Abokor; Janaeya Zuri Baher; Logan Yee; Chung Cheung; Don D. Sin; Emmanuel Twumasi Osei; Emmanuel Twumasi Osei (Frontiers in Medicine)
Mechanical strain plays a significant role in lung pathophysiology. Current two-dimensional (2D) in vitro models fail to capture the lung's dynamic mechanical environment. We developed mechanically strained 2D and more complex three-dimensional (3D) alveolar epithelial-fibroblast co-cultures and organoids using the Flexcell cell stretching bioreactor. To do this we used readily available human A549 epithelial cells and MRC-5 lung fibroblasts to establish 2D and 3D alveolar co-cultures and collagen-I-gel-embedded organoid models in the Flexcell and then strained them at 18% amplitude, 0.4 Hz for 24 h to mimic a pathological environment. The impact of mechanical strain on cell proliferation, morphology, cytoskeletal and tight junctional protein expression, interleukin-6 and-8 (IL-6, IL-8) inflammatory cytokine release, and cell death were assessed. Mechanical strain significantly increased total cell counts in 3D co-cultures but not in 2D co-cultures, potentially signifying increased proliferation. Morphological analysis revealed a marked transition of fibroblasts into broadened shape cells under strain in the 3D co-cultures. This was in line with increased F-actin in 3D co-cultures after strain. The tight junctional protein zonula occludens-1 expression decreased after strain in all 2D and 3D models. Furthermore, exposure to strain increased the release of IL-6 and IL-8. Strain-induced cell death was also elevated across all models, particularly in 3D cultures. This study presents exploratory findings suggesting that in vitro mechanical multicellular alveolar models using the Flexcell system may replicate the dynamic environment of in vivo lung tissue. These multicellular models offer a valuable platform for investigating strain-induced cellular responses relevant to inflammatory and fibrotic mechanisms in lung diseases, particularly in exploring epithelial–mesenchymal interactions that may underlie disease progression.